Anxiety, lexicon, and morphosyntax in instructed L2 Spanish. (4th October 2021) - Kirk, Sadler; Grinstead, John; Nibert, Holly J.
Abstract: Although generalized anxiety has increased among college students, it is unclear what effect this has on language anxiety. While language anxiety has been shown to negatively affect second language achievement, its impact at the level of specific linguistic subdomains has not been evaluated. In what follows, we explore what relationship, if any, exists between Generalized Anxiety Disorder and Foreign Language Anxiety and whether either construct is predictive of L2 Spanish lexical or morphosyntactic development. Results reveal that while foreign language anxiety and generalized anxiety are related, only foreign language anxiety is significantly and negatively predictive of both morphosyntactic and lexical development in the context of instructed L2 Spanish, while general anxiety was only marginally predictive of morphosyntax, but not lexicon. The Challenge: Language anxiety, one of the major obstacles to successful second language acquisition (SLA), has been the object of numerous investigations as both a cause and consequence of language learning difficulty. What relationships exist between language anxiety, general anxiety and the acquisition of lexical and morphosyntactic knowledge in instructed L2 Spanish?